PENGEMBANGAN MEDIA CD PEMBELAJARAN MATA KULIAH FLAT PATTERN DESIGN UNTUK MAHASISWA PRODI PKK TATA BUSANA FT UNP PADANG - Bahri, Halimul; Adriani, Adriani; Novrita, Sri Zulfia (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
This research aims to develop a learning media in the form of CD which can assiststudents in learning Flat Pattern Design by methods Pivot Method. This study is alsoto gain an overview of the feasibility study CD media as a learning medium FlatPattern Design. This study is a Research and Development (Research andDevelopment (R & D) is a research method used to produce a particular product andtest the effectiveness of a particular product. CD learning be tested in the Departmentof Family Welfare to students S1 dressmaking class of 2014 the number of 19 people.The steps undertaken in the development of learning CD media are: 1) pendefenisianstage. 2) design phase, 3) the development stage, at this stage of the development ofdata analysis are: 1) the validity of the data analysis, 2) practicalities of data analysis,and data analysis effectiveness. Based on the results of data analysis that is performedto test the validity of validator that expert instructional media obtained a score of 4,13considered valid and validator matter experts obtained a score of 4,4 can becategorized as very valid, the practicalities of the test carried out to a small group ofstudents obtained a score of 3,8 can be categorized as practical while testing thepracticalities large group obtained a score of 4,03 can be considered a practical andeffective data analysis of student test results before and after using instructional CDmedia increased 20,4% which can be considered effective. The media are in a verydecent criteria used as a medium of learning in terms of the validity of the dataanalysis, the practicalities and effectiveness.Kata kunci: CD pembelajaran, flat pattern design, pivot method